(untitled) (Annals of Medical Research, 2021)
Aim: In this study, we aimed to determine the etiology of syndromic autism with analyzing 50 genes with a targeted gene panel. Cases with a pre-diagnosis of genetic syndrome including autism spectrum disorder were analysed in the current study. Materials and Methods: The targeted gene panel containing fifty genes causing syndromic autism was sequenced using the Illumina NextSeq550 platform. Forty-nine cases with autism spectrum disorder and syndromic clinical findings were analysed after excluding chromosomal abnormalities, microdeletion/duplication syndromes and Fragile X syndrome. Results: Pathogenic/likely pathogenic variants or variants of unknown clinical significance were detected in 26.5% (13/49) of the cases. One case was diagnosed with KBG Syndrome with a de novo pathogenic variant detected in the ANKRD11 gene. Other two pathogenic/likely pathogenic variants were detected in DHCR7 and AMT genes, two cases were accepted as carriers for these genes. Eleven variants of unknown clinical significance were detected in the VPS13B, SETD2, DHCR7, GRIP1, MED12, ALDH5A1, CREBBP, NSD1 and CHD7 genes. Conclusion: In this study, the diagnosis rate was 2%, and the rate of pathogenic/likely pathogenic variant detection rate was 6%, after excluding the cases diagnosed with microdeletion/duplication syndromes and Fragile X Syndrome. Our study is the first study in the literature with 50 genes targeted panel investigating the association of autism spectrum disorder and syndromic disorders with high phenotypic diversity.